Pemenuhan Hak Korban Kekerasan Seksual pada Perempuan melalui Program Sahabat Saksi dan Korban (PUNDIMAS: Publikasi Kegiatan Abdimas, 2023)
Fulfilling the Rights of Female Victims of Sexual Violence through the "Sahabat Saksi dan Korban" Program in the Manggarai Area, where the local residents predominantly work as scavengers and motorcycle taxi drivers, and are economically disadvantaged. The Jendela Kelurahan Manggarai Community in RT.008/01 has undertaken various activities to address this issue, including raising awareness about local regulations and providing support to prevent sexual violence against children and adolescents. (1) The main issue faced by our partners is the need to fulfill the rights of female victims of sexual violence. Most of these victims are housewives (IRT) who have experienced repeated incidents of domestic violence (KDRT). An initial survey was conducted by the proposer at the partner's location on October 26, 2022, to discuss and identify the issues faced by our partners. Based on the results of the field visit to our partners' location, we have outlined a plan for community empowerment. (2) The objective of this service is to protect the rights of female victims of sexual violence. (3) Our methodology includes training, mentoring, workshops, practical exercises, and more for mothers and children in the Manggarai area. The results achieved so far include better protection of women's rights and the psychological and legal recovery of female victims. Through our "Sahabat Saksi dan Korban" program, we aim to create a supportive and empowering environment for female victims of sexual violence, particularly among economically disadvantaged communities like the scavengers and motorcycle taxi drivers in the Manggarai area. Our efforts include raising awareness, providing training and mentoring, and facilitating access to legal and psychological support to ensure that these women can reclaim their rights and lead healthier, more empowered lives.